Analisis Kesehatan Wajah pada Laki-Laki dan Perempuan Usia Produktif di SMA Kalam Kudus II, Jakarta - Tan, Sukmawati Tansil; Wijaya, Bryan Anna; Setiawan, Fiona Valencia; Destra, Edwin (BADAN PENERBIT STIEPARI PRESS, 2024)
Facial analysis plays an important role in early identification of medical conditions through skin changes. Face Analyzer technology offers accurate detection of skin health parameters such as elasticity, hydration, texture and signs of aging. This service activity was carried out at Kalam Kudus High School involving 68 men and women of productive age (18-64 years). Skin measurements using the Skin Analyzer include parameters for pores, spots, wrinkles and roughness. The majority of respondents were aged 18-35 years (52.9%), followed by those aged 36-50 years (27.9%) and 51-64 years (19.1%), with 61.8% female. Data show significant variations in skin parameters based on age, with increased wrinkles and skin roughness at older ages. The results show the importance of early detection and intervention to maintain healthy skin. Regular monitoring and education using advanced technology such as the Face Analyzer can increase awareness and prevention of skin problems. The use of Face Analyzer technology and comprehensive skin health education is very important to improve the skin health of individuals of productive age, prevent skin problems, and improve quality of life.